IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KOMPETENSI TENAGA PENDIDIK PADA PONDOK PESANTREN - Riduwan, Muhammad (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to analyze the implementation of human resource management (HRM) in improving the competencies of educators at Pondok Pesantren Imam Muslim, Sei Rampah District, Serdang Bedagai Regency. Effective HRM is considered crucial to achieve quality educational objectives. This research uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation conducted. The findings of the study show that HRM planning at this Islamic boarding school involves analyzing the needs for educators, strict selection, and development through structured training programs. HRM planning is carried out by mapping out existing tasks and workloads, which are then outlined in the Tupoksi (Job Description and Functions) to ensure that each educator is placed according to their competencies and capacity. This process also includes continuous cadre development, from students (santri) to becoming educators (ustadz). The implementation of HRM at Pondok Pesantren Imam Muslim shows success in the educator selection process, which considers academic achievement, morals, and dedication. However, challenges such as limited facilities and insufficient funding for more intensive training programs remain. Evaluation of educator performance is carried out periodically through weekly, mid-semester, and end-of-year evaluations. Overall, this study indicates that good HRM at Pondok Pesantren Imam Muslim can enhance educational quality and educator competence. Support from the headmaster and the caretaker of the pesantren, as well as the implementation of structured evaluation programs, play an essential role in maintaining the quality of education that continues to develop at this pesantren.